The Dual Effect of Transformational Leadership on Individual- and Team-Level Performance: The Mediational Roles of Motivational Processes - Lu, Hairong; Li, Feng (Frontiers in Psychology, 2021)
Using matched four-stage data from 477 team members and their 132 team leaders in Chinese companies, we examined a cross-level model in which group- and individual-focused transformational leadership (TFL) and their influence affect the team and member performance from the perspective of Chen and Kanfer’s (2006) multilevel model of motivation in teams. The results indicated that group-focused TFL exerts positive effects through sequential mediation of team efficacy and team process whereas individual-focused TFL has a positive effect on team members’ performance through sequential mediation of followers’ self-efficacy and individual regulation process. In addition, we also find significant cross-level mediation effects demonstrating that group-focused TFL was positively related to self-efficacy through the mediator of team efficacy, team efficacy was positively related to the individual regulation process through the mediator of the team process, team process was positively related to individual performance through the mediator of the individual regulation process. Theoretical and applied implications are discussed.